Na marginesie dwu ostatnio opublikowanych nowych czeskich przekładów Nowego Testamentu - Barton, Josef (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
At the beginning of the 20th century, there was a noticeable break (modernization) in the way the Bible was translated in the Czech environment, and thus a visible distancing from the previous (long and rich) tradition of Bible translation into the Czech language. Within the framework of this modern Czech Bible translation, eighteen translations of the entire New Testament and ten translations of the Old Testament (which also means nine complete Bibles) have been produced and published (in addition to many translations of smaller parts of the Bible) in the course of about one hundred years. The article presents two modern recently-published Czech translations of the New Testament (published in 2013 and 2020), each representing a significantly different methodological approach. In particular, the article shows the salient features of their authors’ work with the Czech language, the attempts to outline the contours of their grasp of biblical style, and suggests possible inspirations that future translators could draw from these translations.